The Role of Supportive Leadership in Human Resources flexibility An Analytical Study of the Opinions of a Sample of Staff at Akre University of Applied Sciences - Abdullah Hassan, Mikael; Ahmed Khader, Shihab (Iraqi Journal for Administrative Sciences, 2025)
This research aims to examine the role of supportive leadership in enhancing human resource flexibility at Akre University of Applied Sciences. The study focuses on dimensions of supportive leadership (employee empowerment, inspirational motivation, and fairness in treatment) and their relationship with aspects of human resource flexibility (behavioral flexibility, skill flexibility, and HRM practice flexibility). Data were collected from a sample of 200 employees using a questionnaire and analyzed using SPSS V.23. The results revealed a statistically significant relationship between supportive leadership and human resource flexibility, indicating that leadership plays a key role in enhancing employees' adaptability to challenges. The research recommends developing sustainable training programs to empower human resources and improve institutional performance.